Non specific acute abdominal distress.: Estudio prospectivo - Guicheff, Vladimir (Cirugía del Uruguay, 1987)
A prospectiva study of 226 patients that consulteél in Emergency Department for non specific acule abdominal pain is presentad. The follow up was achieved in 194 cases. This entity accounts for 28% of the cases makes us think in the possibility of unnecessary surgery in case of acule abdominal distress. We have no doubts in performing al the least idea of its usefulness.